Market deregulation, trade liberalization and productive efficiency in Bangladesh agriculture: an empirical analysis - Salim, Ruhul; Hossain, A. (Routledge, 2006)
The impact of trade liberalization and of market deregulation in general, on the performance of agriculture remains contentious and empirical issue in the literature. Following the random coefficient frontier modelling framework, this paper attempts to contribute to this debate by computing the farm-specific productive efficiency indices in Bangladesh agriculture before and after reform. It also examines the impact of some farm-specific and policy variables on productive efficiency. The empirical results show that there are wide variations in productive efficiency across farms and regions and the average efficiency of all regions increased modestly by 8 percentage points from the pre-reform to post-reform period. The efficiency differentials are largely explained by farm size, infrastructure, households' off-farm income and the reduction of government anti-agricultural bias in relation to trade and domestic policies. The implication of these results suggests the need for further policy reform to augment productive efficiency.